2019
DOI: 10.3390/s19153360
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Bulk Piezoelectric Acceleration Sensor for Enhanced Performance

Abstract: While seeking to achieve high performances of a bulk piezoelectric acceleration sensor, we investigated the behavior of the design variables of the sensor components and optimized the sensor design using a numerical simulation based on piezoelectric analysis and metamodeling. The optimized results demonstrated that there was an exponential dependency in the trade-off relation between two performance indicators, the electric voltage and the resonant frequency, as induced by the design characteristics of the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Details on these optimization processes as well as all the material data used for numerical analysis were described in ref. [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details on these optimization processes as well as all the material data used for numerical analysis were described in ref. [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our recent numerical investigation found that in constructing an accelerometer, the performances of these two characteristics were significantly influenced by the design factors (geometry, dimensions and configuration) of the components (e.g., seismic mass, piezo element, tail, base and insulating layer etc.) [ 10 ]. To obtain better performances, moreover, it was necessary to carefully choose the component design by optimizing the design variables of each component, which was possible by thoroughly understanding the relationship between the design characteristic and the physical functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1b, the tester included three main parts: the ambient temperature control section, the cable-grinding drive, and the cable friction force piezoelectric sensor. [15][16][17]. The surface and chips of the wear obtained from the test were analyzed by a microscope.…”
Section: Experiments Systemmentioning
confidence: 99%
“…The cable's insulation layer is made of polyvinyl chloride-based polymer. A flexible cable friction and wear test system designed to carry orthogonal friction experiments, and the friction forces of the cables have been recorded by the piezoelectric sensor [15][16][17]. The surface and chips of the wear obtained from the test were analyzed by a microscope.…”
Section: Introductionmentioning
confidence: 99%